2014
DOI: 10.7883/yoken.67.22
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxidative Stress and Total Thiol Levels in Crimean-Congo Hemorrhagic Fever

Abstract: In this study, we investigated the pro-and antioxidant status of patients with a pathogene-sis of Crimean-Congo hemorrhagic fever (CCHF) in terms of their role in its pathogenesis. During the study period, 34 children and 41 adults were diagnosed with CCHF. The control group consisted of healthy age-and gender-matched children and adults. Serum levels of the total antioxidant capacity (TAC), total oxidant status (TOS), oxidative stress index (OSI), and plasma total thiol (TTL) were evaluated and compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
5
15
0
Order By: Relevance
“…In this study it was ascertained that native thiol levels, though insignificant, proved to be lower in the patient population. In the previously conducted studies, it was shown that native thiol level decreased in the presence of infections such as brucellosis as well as Crimean-Congo haemorrhagic fever and viral and bacterial tonsillopharyngitis [8,22,23]. The results of present study are in agreement with the studies in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…In this study it was ascertained that native thiol levels, though insignificant, proved to be lower in the patient population. In the previously conducted studies, it was shown that native thiol level decreased in the presence of infections such as brucellosis as well as Crimean-Congo haemorrhagic fever and viral and bacterial tonsillopharyngitis [8,22,23]. The results of present study are in agreement with the studies in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress is evaluated as responsible for the etiopathogenesis and pathophysiology of many diseases (7)(8)(9). Reactive oxygen species (ROS) production occurs immediately after exposure to oxidative stress and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…ratio between TOS and TAS indicating disturbance in antioxidant status which may contribute to hepatic degenerative changes. 32 Cellular antioxidant defense consists of non-enzymatic (thiols, antioxidants, etc) and enzymatic (CAT, SOD, GPx, GST) components, which contributes a crucial role in free radicals induced cellular damage. Reduction in levels of TTH and activities of antioxidant enzymes on APAP administration indicates reduction in level of TAS.…”
Section: Discussionmentioning
confidence: 99%